The Prevalence of Gingival Recession According to the Cairo Classification in a Population from the North of Portugal - Beatriz Moura; Filomena Salazar; Rosana Costa; Cristina Cabral; Cátia Reis (Dentistry Journal)
Background/Objectives: Gingival recession (GR) has a multifactorial etiology, resulting from the interaction of various factors. It affects aesthetics and comfort, and has negative consequences for quality of life. The main objective of this study is to investigate the prevalence of gingival recession in a sample of the population in northern Portugal, according to the classification system proposed by Cairo. The secondary objective is to investigate possible risk factors for the prevalence of gingival recession. Methods: This observational study analyzed 50 patients who met all our inclusion criteria. Participants underwent a clinical periodontal examination and completed a questionnaire. Results: On the lingual/palatine side, recession type 2 (RT2) was the most prevalent (39.1%), and on the buccal side, recession type 3 (RT3) was the most prevalent (37.7%). Statistically significant differences were found in the occurrence of RT3 on both sides, buccal and lingual/palatine, which was higher in patients over 65. Buccal side RT2 and buccal and lingual/palatine side RT3 were more prevalent in males. Buccal side RT2 was more prevalent in ex-smokers compared to nonsmokers. RT3 was more prevalent in ex-smokers compared to smokers and nonsmokers. Most patients have gingival recession with loss of interproximal attachment. Conclusions: Older age, male gender, high plaque levels, and smoking habits are considered risk factors.